2016
DOI: 10.3390/en9121029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind Turbine Blade Rotation on Triggering Lightning: An Experimental Study

Abstract: Abstract:Compared with other lightning targets on the ground, the most notable feature of a wind turbine is that the blades are usually in a rotating state when lightning strikes. To study the mechanism of blade rotation influencing wind turbine on triggering lightning, lightning discharge comparison tests based on a typical 2-MW 1:30-scaled wind turbine model with an arching high-voltage electrode were conducted under different modes of stationary and rotating blades. Negative polarity switching impulses of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In this experiment, two models of typical 2‐MW wind turbines are designed at a scaled ratio of 1:30. The model mainly comprises the body, blade, and power transmission component …”
Section: Test Set Upmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experiment, two models of typical 2‐MW wind turbines are designed at a scaled ratio of 1:30. The model mainly comprises the body, blade, and power transmission component …”
Section: Test Set Upmentioning
confidence: 99%
“…Because of the structural characteristics and rotation characteristic of the blades, the position when the discharge hits the wind turbine is different under each discharge So, to ensure that the distance from the blade tip to the high-voltage electrode is always the same when the blades are rotating, arc-shaped high-voltage electrodes suitable for 1-, 2-, 4-, 6-, and 8-m gaps are designed and manufactured. [21][22][23][24] The length of the blade is 1.25 m. The dimensions of the arc-shaped high-voltage electrodes for different gaps are presented in Table 1.…”
Section: High-voltage Electrode Designmentioning
confidence: 99%
See 1 more Smart Citation
“…As a supplementary means of protection in case of uncertainty in the behavior of such system with metal receptors and internal down‐conductors, low voltage surge arresters are proposed to reduce transient overvoltage in the low voltage network . Meanwhile, the fact that the rotation of the blades makes it easier to trigger lightning is verified . Although techniques for thundercloud approach prediction are proposed, they are not that accurate, or too expensive to be employed widely .…”
Section: Introductionmentioning
confidence: 99%
“…Madsen [25] established a mathematical model for calculating the time and space distribution of the electric field around the blade under the excitation of the downward leader, and a 3-D model of the risk assessment for the blade lightning was established. Wen et al [26] studied the effect of wind turbine rotation on triggering lightning was via the high voltage discharge test method. The analysis showed that the blade rotation could be altering the charge distribution on the blade tip, resulting in varied ascending leader development on the blade tip, which affected the discharge development process.…”
Section: Introductionmentioning
confidence: 99%